Dua Sisi Perilaku Kepatuhan Wajib Pajak Dalam Bisnis E-Commerce - I Gusti Agung Ayu Surya Andanari; Gede Sri Darma (RELASI : JURNAL EKONOMI, 2022)
This research aiming to perceive how the transparency of e-commerce business owner as a tax payer toward the goverment regulation, knowing the factors that support and hinder the compliance of e-commerce business actors in reporting their income taxes and the impacts generated by the lack transparency of tax payer (e-commerce business owner). Theory that is used in this research is a Compliance Theory from Taylor. This research is using a descriptive qualitative method. Data collection is done by observation nonpartitipative, deep interviews and documentation study. The results of this study indicate that there are still many e-commerce business actors in Denpasar City who do not comply with the policies that have been made by the government. The factors that hinder e-commerce business actors from reporting their income taxes include information, rewards, and environmental factors. Meanwhile, the factors that support taxpayer compliance in reporting their income tax are information, coercion, and ideology factors. The impact of the lack of taxpayer compliance (e-commerce business actors), including the impact on state finances, namely a decrease in income, especially for regional budget revenues from taxes, and of course this also has an impact on the e-commerce business itself in the form of account blocking. and imposition of fines. Keywords: Compliance, Tax, E-Commerce, Bali.